2020
DOI: 10.3390/toxins12100636
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Levels of Naturally Multi-Contaminated Feed with Fusarium Mycotoxins on Broiler Chickens and Evaluation of the Mitigation Properties of Different Titers of Yeast Cell Wall Extract

Abstract: The chronic intake of naturally multi-mycotoxin contaminated feed by broilers with or without titers of Yeast Cell Wall Extract (YCWE, a.k.a Mycosorb A+®), was investigated. Day-old male Cobb chicks (1600 birds, 64 pens, 25 birds/pen) were randomly allocated to diets of control (CON); diet containing mycotoxins (MT); CON + 0.2% YCWE; MT + 0.025% YCWE; MT + 0.05% YCWE; MT + 0.1% YCWE; MT + 0.2% YCWE; and MT + 0.4% YCWE. Growth performance, blood biochemical parameters and gut health were recorded over 42 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 31 publications
5
17
1
Order By: Relevance
“…Avantaggiato et al [42] utilized an in vitro GI-model for pigs to demonstrate that the majority of DON is absorbed in the jejunum, with lesser amounts in the ileum. Although research has demonstrated that the damages of DON to the gastrointestinal tract morphology of monogastric animals can occur [35,43,44], the results from our current trial show the effects of DON in a pair-feeding setting. As a result, the negative impacts on the morphology of the intestinal tract provide evidence suggesting that damages may be a direct toxic effect of DON rather than a reduction in feed intake.…”
Section: Discussioncontrasting
confidence: 73%
“…Avantaggiato et al [42] utilized an in vitro GI-model for pigs to demonstrate that the majority of DON is absorbed in the jejunum, with lesser amounts in the ileum. Although research has demonstrated that the damages of DON to the gastrointestinal tract morphology of monogastric animals can occur [35,43,44], the results from our current trial show the effects of DON in a pair-feeding setting. As a result, the negative impacts on the morphology of the intestinal tract provide evidence suggesting that damages may be a direct toxic effect of DON rather than a reduction in feed intake.…”
Section: Discussioncontrasting
confidence: 73%
“…A meta-analysis by Holanda and Kim [ 23 ] showed that the consumption of 1000 µg/kg DON by pigs reduced average daily gain by 8.9% while House et al [ 24 ] indicated that the same concentration of DON could significantly increase the number of days required for female pigs to reach 110 kg. Broilers consuming feed with DON at 2264 µg/kg have also shown reduced gain and increased feed conversion ratio [ 25 ]. In dairy cows, it is suggested that cows consuming dietary DON ≥ 6740 µg/kg can have 3.7 times greater abortion rates while dietary DON ≥ 3210 µg/kg may increase the percent of cows with endometritis by 1.9 times [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple in vivo studies of various animal species have shown the mitigation capabilities of binders following the administration of synthetic or natural mycotoxins via diet, whereas the binder’s efficacy has been appraised based on an observed improvement in animal performance [ 26 , 27 , 28 ]. Other animal studies have primarily focused on indirect, often non-specific/shared biomarkers of exposure as an outcome in the evaluation of mitigation strategies, such as measuring changes in intestinal health using histopathological assessment [ 29 ], modification of blood chemistry [ 30 , 31 , 32 , 33 ], changes in immunological titers [ 34 , 35 , 36 , 37 , 38 ], changes in microbiota [ 32 , 39 ], genomic and antioxidant markers [ 40 , 41 , 42 , 43 ], and changes in organ morphology [ 44 , 45 ]. However, only a few in vivo studies have measured toxin partitioning in the animal body and revealed the pharmacokinetics of toxin accumulation in different tissues and digesta [ 46 , 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%